The Spectacular Past: Popular History and the Novel in Nineteenth-Century France - Samuels, Maurice (Cornell University Press, 2004)
Struggling to make sense of the Revolution of 1789, the French in the nineteenth century increasingly turned to visual forms of historical representation in a variety of media. Maurice Samuels shows how new kinds of popular entertainment introduced.